Medical Aesthetic Practices from The Perspective of Legal Liability to Achieve Equitable, Inclusive, and Sustainable Health Care - Ineke Winda Ferianasari (Jurnal Sosial Teknologi, 2026)
The practice of medical aesthetics in Indonesia is growing rapidly alongside advances in healthcare technology and the public’s increasing demand for appearance-enhancing treatments. Aesthetic procedures such as aesthetic dermatology, cosmetic injections, and cosmetic surgery have become part of modern healthcare services aimed at improving quality of life. However, aesthetic procedures performed on healthy individuals raise legal implications, particularly regarding the liability of medical personnel in the event of complications or unsatisfactory outcomes. Article 274 of Law No. 17 of 2023 on Health stipulates that medical personnel are obligated to provide services in accordance with professional standards, service standards, standard operating procedures, and professional ethics. Nevertheless, medical aesthetic practices still face challenges regarding the clarity of legal liability in the provision of their services. This study aims to (1) analyze the legal framework governing medical aesthetic practices within Indonesia’s health law system, and (2) examine the forms of legal liability for medical professionals in medical aesthetic practices to achieve equitable, inclusive, and sustainable healthcare services. The research method used was a normative legal approach, employing both a statutory and a conceptual framework. The results of the study indicate that the regulation of medical aesthetic practices within the Indonesian health law system establishes professional standards and medical service standards as the primary foundation for the provision of health services.